PROSES BERPIKIR KRITIS SISWA DALAM MENYELESAIKAN MASALAH PEMODELAN ALJABAR DITINJAU DARI GENDER DAN SELF-CONCEPT - Fatkur Rochmah; Alifiani; Abdul Halim Fathani (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2026)
Mathematics is important to learn to develop students’ abilities and potential. The study describes the critical thinking process of seventh-grade students at MTS Wahid Hasyim 2 Dau on the material of quadrilaterals, viewed from the perspectives of gender and self-concept. The study was conducted on May 22, 2026, using descriptive methods and qualitative approaches. The subjects of this study were 3 male students (1 student with a high self-concept category, 1 student with a medium self-concept category, and 1 student with a low self-concept category), for female students consisting of 3 students (1 student with a high self-concept category, 1 student with a medium self-concept category, and 1 student with a low self-concept category). Data were collected through a mathematical critical-thinking ability test on problem solving and interviews, and then analyzed based on indicators of understanding problems (interpretation), identifying relationships between concepts (analysis), using appropriate strategies (evaluation), making conclusions (inference), and providing reasons for choosing conclusions (explanation). The results of the study indicate that critical thinking processes differ by level of self-concept and gender. A positive self-concept plays a crucial role in supporting students' critical thinking skills. Gender differences are more evident in problem-solving characteristics, with male students tending to be quicker and more concise, while female students are more thorough, systematic, and neat in solving math problems.